Is unemployment always higher when insiders decide? - Trine Filges; Birthe Larsen (Copenhagen Business School (CBS), Department of Economics, 2000)
This paper challenges the traditional view that unemployment is high because insiders determine the union wage. The insiders in this paper are characterized by being more efficient when they search for a job than the outsiders, implying that they experience relatively less unemployment. We assume that wages are determined by a monopoly union and further that a union leader is elected by a majority voting rule. Insiders may prefer a lower wage than outsiders, implying the possibility of lower unemployment.
hdl:10398/7573
Keywords: J20; J50; J60; 330; Insiders and Outsiders; Search; Unemployment